2002
DOI: 10.3136/fstr.8.311
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cation Sequestering and pH on Quiescent Thermal Association of .BETA.-Lacto-globulin NB from Fresh Cheddar Whey: An Insight into Gelation Mechanism.

Abstract: Freshly fractionated ␤-lactoglobulin AB (␤-Lg) from Cheddar whey was dispersed at pH 3.5, 7, and 9 buffers containing 20 mM EDTA, and circulated at 25˚C through a closed loop containing a 200 nm pore size membrane, to remove traces of dust and large aggregates, and an water jacketed cuvette placed within a Dynamic Light Scattering (DLS) device for real-time data acquisition. Filtered samples were step-wise heated from 25˚C to 90˚C with continuous data acquisition to study dynamic changes in mean aggregate diam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Between pH 2.0 and 3.7 b-lg has been reported to form dimers (Pessen, Purcell, & Farrell, 1985). Haque and Sharma (2002) also found by DLS that at pH 3.5 b-lg showed a tendency to association. CMP (4%, pH 3.5, deionized water) presented a higher degree of association at pH 3.5 as compared with neutral pH, with maximum values of the predominant lower size peak at 6 nm ( Fig.…”
Section: Size Distribution Of Particles At Ph 35mentioning
confidence: 77%
“…Between pH 2.0 and 3.7 b-lg has been reported to form dimers (Pessen, Purcell, & Farrell, 1985). Haque and Sharma (2002) also found by DLS that at pH 3.5 b-lg showed a tendency to association. CMP (4%, pH 3.5, deionized water) presented a higher degree of association at pH 3.5 as compared with neutral pH, with maximum values of the predominant lower size peak at 6 nm ( Fig.…”
Section: Size Distribution Of Particles At Ph 35mentioning
confidence: 77%
“…This would hypothetically orient their hydrophobic tails toward solvent molecules. In another study, we observed that at 22˚C, β-lactoglobulin asso-ciated in the presence of trace peptides to give a large aggregate distribution [25].…”
Section: Resultsmentioning
confidence: 99%
“…This effect is attributed to the lower content of total solids in the M1DF and M2DF products (Table 2) since DF in UF membranes removes lactose and milk minerals. When milk solids like minerals, specifically the calcium is removed from the casein micelles, acid gels with higher loss tangents (tan δ) are generated, which explains their lower springiness (Haque & Sharma, 2002;Ozcan et al 2011).…”
Section: Resultsmentioning
confidence: 99%